(untitled) (Research, Society and Development, 2020)
This article analyzes the female representation of candidates for the Municipal Executive in Rio Grande do Norte (RN) from 1996 to 2016. The purpose of the analysis is to assess whether the state has pioneered female candidates, estimating whether there has been an evolution in the number of candidates, which parties presented more women in the race and the profile of those who managed to be elected in the 2016 municipal election. We tested the pioneering hypothesis to outline RN as a state that demonstrates significant numbers on female participation, strained the theses that point in Brazil a strong underrepresentation (Miguel, 2003; Sachet, 2013; Assis, 2017), due to institutional and structural factors, such as: political culture, electoral system, campaign financing, etc. The study is based on the laws that guarantee a mandatory percentage for the registration of female candidates (Laws 9,100 / 95 and 9,504 / 97), as well as the availability of data in the repository of the Superior Electoral Court. As a result, it was possible to notice that there was an increase in the numbers of women candidates and elected in the municipalities of RN in the last 20 years, which converges to an understanding that the laws suggested the female participation and that the parties that obtained good numbers of candidates they are situated ideologically in the center and to the right of the Brazilian political spectrum. In addition, it was possible to notice that the profile of the mayors elected in 2016, mostly, is white, married, middle-aged women (40-59 years) and complete higher education.